A quantitative study on zero copula in Japanese. (March 2023) - Nambu, Satoshi
Abstract: This article investigates the nature of zero copula in Japanese from variationist sociolinguistic and historical perspectives. The corpus-based surveys revealed that zero copula has existed for a long period of time and used to be the default form in the relevant linguistic environments in the past, which currently undergoes a change toward an increase in the use of the overt copula. The questionnaire survey confirmed that the overt copula is considered the correct form as the norm of Japanese, and that zero copula is not linked to the casualness of speech unlike the case of copula omission. The discrepancy between the norm and the historical trajectory suggests that the change involves two stages: a change in grammar followed by a change from above. Regarding the change in grammar, a hypothesis was proposed as to how the change has progressed by drawing attention to the reanalysis of the structure with the particle to and subject markers related to the ECM construction. Highlights: From variationist sociolinguistic and historical perspectives, this study elucidates the nature of zero copula in Japanese. This study confirmed that the overt copula is regarded as the correct form in comparison to zero copula. This study revealed that zero copula used to be the default form in the history of Japanese and its use has been decreasing over time. The quantitative data suggests that the change involves two stages: a change in grammar followed by a change from above.